Das Alte Testament und seine bildliche Repräsentanz in byzantinischen Kirchen: Einige grundlegende Überlegungen - ALTRIPP, Michael (Byzantina Symmeikta, 2022)
In Early Christian and Byzantine pictorial cycles there is nothing like the typological order found in Western churches of Medieval times. Instead the context of OT settings in Byzantine art shows a different relation between OT and NT. It is caracterized by a continuum which makes the OT tradition a very important part that is not surpassed by the NT. Furthermore OT and NT are part of a history that has its telos in the future. This thesis and its implications for Byzantine art is laid out in this paper and has to be validated by further research.